Faulty parallel structure in students’ argumentative writing - Asti Ayuningsih; Sri Widyarti Ali; Fahria Malabar (TRANSBAHASA, 2020)
In writing, to produce well-structured and understandable sentences, students must have knowledge of one aspect of grammar, namely parallelism. However, in fact, many students do not understand the concept of parallelism so that they fail to apply it in writing. This study examines the common types of faulty parallel structure in students’ argumentative writing and investigates the factors which cause the fault. This is a qualitative study that collects the primary data from students’ argumentative writing in particular topics which demand them to present their arguments and to provide their position, reasons and evidence in their writing, and the secondary data from the interview. As a result, this study discovers that students commit the faults in different types of parallelism, and mostly take place in parallel structure with elements joined by conjunction, both coordinating and correlative conjunction. The result of the interview section shows that students make the faulty parallelism due to lack of knowledge, lack of attention, and lack of vocabulary. Thus, in order to reduce the faulty parallel structure, the specific materials about parallelism should be added in writing or grammar’s lesson plan.